Australia's Indonesia Project 50 years of engagement - Brown, Colin 1949- (Bobby Graham Publishers Pty Ltd, 2015)
This 50-year history of the Australian National University's Indonesia Project takes the reader from HW Arndt's 1964 visit to Sukarno's Indonesia, where politics trumped economics, through Soeharto decades of technocratic policy making to the strong and multi-faceted engagement of the Project's scholars with the economists and policymakers of today democratic state.